A Framework for Secure eHealth Data Privacy Preserving on Block chain with SHA-256 in Cloud Environment (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Safeguarding the eHealth information of patient’s stands utmost paramount for performing web-scaleanalytics and reporting applications. Apparently, there has been data breaches that have become quite prominentlately. The prime target is towards resolving the issue of determining robust and trustworthy analytics in asecured way that fulfills product pre-requisites. There is proposal of an improved version of eHealth dataprivacy preserving system apt for the cloud space. The proposed system yields in at par integration,interoperability, availability as well as sharing of healthcare information amidst various healthcare providers,patients, and practitioners. There is distribution of patient’s health details amidst the various Treatment ServiceCompany which are combined and put away in the cloud space thus building the patient’s overall eHealthinformation. Cloud technology benefits by providing prompt Internet access as well as feasible access toeHealth information from any location and platform at any given time. There has been a significant rise in thevolume of the healthcare information produced as well as the difficulty involved in its data type. To resolve this,technique of blockchain has been recommended for determining effective measures by the practitioners at theright time. Moreover, the proposed system imbibes certain important security constraints and access controlmechanism that ensures security, integrity, and protection of Ehealth information via blockchain using SHA-256. Above all, the said system encourages development of a system that is economical, highly efficient andsecure.